The legacy of Stonewall : an exhibition on the history of New York's lesbian and gay communities. (New York : The New York Public Library, 1994)
Fonds Suzan Daniel (FSD)
Engels
Brochure
Keywords: tentoonstellingen; lesbische vrouwen; homoseksualiteit; New York